2010
DOI: 10.3102/0013189x10363171
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Consequences of Cognitive Functioning Across the Life Course

Abstract: Research on variation in cognitive abilities has focused largely on their genetic or experiential sources and on their economic consequences. This article takes a broader look at the consequences of cognitive ability—IQ—across the life course. Contrary to received wisdom, the effects of IQ on economic success are almost entirely mediated by educational attainment. Among persons with equal levels of schooling, IQ has little influence on job performance, occupational standing, earnings, or wealth. But there are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 78 publications
(98 reference statements)
3
37
0
4
Order By: Relevance
“…First, it is mathematics focused, with self-beliefs and values measured specifically in this domain. This is not unusual in this sort of research and mathematics is an important domain in explaining long-term attainment (Buchmann & Park, 2009;Hauser, 2010). Nevertheless, self-beliefs are domain specific and, as such, further research should consider the information distortion model in relation to other academic domains and in relation to global academic domain variables.…”
Section: Limitationsmentioning
confidence: 95%
“…First, it is mathematics focused, with self-beliefs and values measured specifically in this domain. This is not unusual in this sort of research and mathematics is an important domain in explaining long-term attainment (Buchmann & Park, 2009;Hauser, 2010). Nevertheless, self-beliefs are domain specific and, as such, further research should consider the information distortion model in relation to other academic domains and in relation to global academic domain variables.…”
Section: Limitationsmentioning
confidence: 95%
“…Cognitive ability is positively correlated with earnings, although the strength of this correlation and the degree to which the effect is direct or mediated by educational attainment is unclear (Cawley et al 1997; Cawley, Heckman, and Vytlacil 2001; Gensowski 2014; Hauser 2010; Heckman et al 2006). Heckman and colleagues (2006) estimate that cognitive ability explains 9 percent of the variance in men’s wages and 12.4 percent of the variance in women’s wages.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given increases in the importance and costs of higher education, we focus explicitly on the transition from high school into and through college, including pathways into elite colleges. We build on a substantial evidentiary foundation that demonstrates how cognitive skills—including quantitative and verbal ability—and noncognitive skills—including self-esteem, locus of control, and self-concept—contribute to (parental) income and wealth (e.g., Fletcher 2013; Hauser 2010; Heckman, Stixrud, and Urzua 2006; Mayer 1997; Zagorsky 2007). As we will show, these same parental skills contribute to children’s educational success, and thus to an appreciable degree confound the association between parents’ economic resources and children’s educational outcomes.…”
mentioning
confidence: 99%
“…However, there are other, sometimes surprising, consequences of IQ throughout adult life. The long-term correlates of adolescent cognition include drinking behaviour, survey participation, Internet use, and the timing of menopause (Hauser, 2010). Some early and recent studies have further shown a negative relationship between intelligence and religious belief in the United States and Europe (Lynn et al 2008), as well as childhood obesity (Yu et al 2010), and fertility (Meisenberg, 2010).…”
Section: Introductionmentioning
confidence: 98%